2021
DOI: 10.1371/journal.pone.0257211
|View full text |Cite
|
Sign up to set email alerts
|

Saffron extract attenuates neuroinflammation in rmTBI mouse model by suppressing NLRP3 inflammasome activation via SIRT1

Abstract: Traumatic brain injury (TBI) remains a major cause of morbidity and disability worldwide and a healthcare burden. TBI is an important risk factor for neurodegenerative diseases hallmarked by exacerbated neuroinflammation. Neuroinflammation in the cerebral cortex plays a critical role in secondary injury progression following TBI. The NOD-like receptors (NLR) family pyrin domain containing 3 (NLRP3) inflammasome is a key player in initiating the inflammatory response in various central nervous system disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 89 publications
2
15
0
Order By: Relevance
“…Glial fibrillary acidic protein (GFAP), ionized calcium-binding adaptor molecule 1 (Iba1) are major markers of astrocyte and microglial activity respectively 40 , 41 and neuronal nuclei (Neu N) acts as a neuronal damage marker 42 . In our recent study 43 , the expression levels of these markers were measured to assess the head injury and an increase in their expression levels was observed in the TBI group confirming induction of astrocyte, microglial activation, and neuronal injury.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Glial fibrillary acidic protein (GFAP), ionized calcium-binding adaptor molecule 1 (Iba1) are major markers of astrocyte and microglial activity respectively 40 , 41 and neuronal nuclei (Neu N) acts as a neuronal damage marker 42 . In our recent study 43 , the expression levels of these markers were measured to assess the head injury and an increase in their expression levels was observed in the TBI group confirming induction of astrocyte, microglial activation, and neuronal injury.…”
Section: Discussionmentioning
confidence: 82%
“…Sirtuin 1 (SIRT1) is also an essential element for normal cognitive function and synaptic plasticity 67 and proved to enhance cognitive dysfunction in many studies 68 , 69 . The measured SIRT1 levels were also suppressed post TBI 43 . In alignment with our data, inhibition of NLRP3 inflammasome has shown to play a crucial part in ameliorating the cognitive deficits induced in diabetic rats following ischemia 70 , encephalomyelitis 71 , AD models 68 , and TBI models 72 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Shaheen et al. reported that saffron attenuated neuroinflammation in TBI mouse model by suppressing NLRP3 inflammasome via SIRT1 activation ( 49 ). Li et al.…”
Section: Discussionmentioning
confidence: 99%